Chemical Composition of Crop Contents of Local Scavenging Chickens - Rashid, Mahbubur; Roy, Bibek Chandra; Asaduzzaman (Pakistan Journal of Nutrition, 2003)
The study assessed the chemical compositions of the crop contents of local chickens. A total of 70 local scavenging chickens (35 layers and 35 growers) were collected from rural areas of Bangladesh and were sacrificed. After dissection of the crops, the contents were dried under sunshine and ground and the ground contents of each crop were chemically analyzed. The mean weight of dried crop contents was 19.9±4.56 g for layer and 13.4±2.62 g for grower. The mean dry matter (DM) percentage of crop contents was 45.5±7.40 for layer and 48.9±7.06 for growers. The mean (% of DM) crude protein (CP), ether extract (EE), crude fibre (CF), ash, nitrogen-free-extract (NFE), calcium (Ca) and total phosphorus (P) of the crop contents were 11.7±2.53, 2.07±0.954, 6.04±2.98, 12.4±5.51, 68.3±7.80, 1.32±0.793 and 0.459±0.177, respectively for layers and were 9.89±1.59, 2.11±2.21, 6.40±4.30, 12.3±6.71, 69.3±7.95, 0.761±0.406 and 0.336±0.200, respectively for growers. The calculated metabolizable energy (ME) was 2781±336 and 2755±441 kcal/kg DM for layers and growers, respectively. Crude protein, Ca and P contents were significantly higher (P